Measuring The Effect Of Work-Life Balance on Employee Performance Through Job Satisfaction In Employees In The City Of Bandung - Mamun Sutisna; Yayan Firmansyah; Salma Shabira Rahmadanti (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Work-life balance is often a factor that prospective workers or workers are looking for in order to stay with their current company. This can affect employee performance and their job satisfaction. This study was conducted to find out how much work-life balance (X) has an effect on job satisfaction (Z) and its impact on employee performance (Y) on employees in the city of Bandung. The respondents were taken based on the criteria of active employees of a company in the city of Bandung. The data analysis method in this study uses SmartPLS software. Testing the daa through validity, reliability, hypothesis, and mediation tests. Based on the results of the study, it was shown that the work-life balance variable had a significant effect on employee performance, the work-life balance variable had a significant effect on job satisfaction, the job satisfaction variable had a significant effect on employee performance, and the work-life balance variable had a significant effect on employee performance through job satisfaction. The level of employee performance can be maintained by paying attention to the work-life balance and employee job satisfaction because these three things are interrelated. The company may add or update its regulations or facilities to support this